A Single Solid That Can Generate Two Impossible Motion Illusions. (September 2014) - Sugihara, Kokichi
We discovered three-dimensional solids that can generate two different impossible motion illusions. When such a solid is seen from two particular viewpoints, two different shapes are perceived. In both cases the perceived physical motion appears to be impossible.